PENGARUH AKUNTABILITAS , GAYA KEPEMIMPINAN, KOMPENSASI FINANSIAL, DAN LOCUS OF CONTROL TERHADAP KINERJA PEMERIKSA PAJAK - Anuar, Rizky Guspendri; -, Zirman; Ali, Al Azhar (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This study aimed to examine the effect caused by the variable accountability, leadership styles, financial compensation, and locus of control tax inspectors in the performens of inspector in KPP Madya Pekanbaru, KPP Pratama Pekanbaru Tampan, KPP Pratama Pekanbaru Senapelan dan KPP Pratama Bangkinang. Respondents in this research were 51 tax inspectors. Data collection techniques in this study is in the form of questionnaires, while data analysis technique used is multiple regression analysis were processed with SPSS version 20.0 for Windows. From the results of the testing that has been done, simultaneous regression test (F test) showed that all independent variables studied have a simultaneous effect on the variable performens of inspector. Partial regression test (t test) showed that independent variables accountability, leadership styles, financial compensation had partial effect on the variable performens of inspector. Meanwhile variable locus of control haa not effect. The magnitude of the effect caused by Adjusted R2 by four variables together against the dependent variable 64.9%, while the remaining 35.1% is influenced by other variables not examined in this study.Keywords: Accountability, Leadership,Compensation, Locus of Control, and Tax Inspectors.